Kesiapsiagaan Rumah Sakit Umum Daerah Haji AbdoelMadjid Batoe Batanghari Jambi Menghadapi Bencana - Herlina J. EL- Matury; Shintya Handayani; Megawati Sinambela; Aprilius Simanjuntak; Rahmad Gurusinga (STIKes Hang Tuah Pekanbaru, 2021)
Disasters are events caused by events or a series of events caused by natural or non-natural. During the period from January to May 2021, there were 1,185 disasters that occurred in Indonesia such as floods, tornadoes, landslides, forest and land fires, earthquakes, tidal waves and droughts. This study aimed to analyse the preparedness of the Haji Abdoel Madjid Batang Hari Regional General Hospital (RSUD HAMBA) Jambi (facing disasters and the COVID-19 pandemic). The research method uses a mix method approach, using the Hospital Safety Index (HSI) forms. The HAMBA Hospital included earthquakes, strong winds, fires, and the COVID-19 pandemic. The struktural safety assessment got an index score of 0.69, non-struktural safety was 0.67, and emergency and disaster management safety got an index score of o.63. Overall, HAMBA Hospital received a safety index of 0.67 which was included in the